Shocking HIV-1 with immunomodulatory latency reversing agents. (January 2021) - Kula-Pacurar, Anna; Rodari, Anthony; Darcis, Gilles; Van Lint, Carine
Highlights: Targeting specific receptors on immune cells with immunomodulatory agents represents a promising way to reverse rever HIV from latency. Immune checkpoint blockers, toll-like receptor agonists, cytokines and CD8 + T cell depleting antibodies reactivate HIV-1 from latency. The exact molecular mechanisms by which immunomodulatory LRAs reverse latency remain incompletely understood. A deeper understanding of immunomodulatory LRAs' mechanisms of action should result in more effective and safer HIV cure strategies. Abstract: The "shock-and-kill" strategy is one of the most explored HIV-1 cure approaches to eliminate latent virus. This strategy is based on HIV-1 reactivation using latency reversing agents (LRAs) to reactivate latent proviruses (the "shock" phase) and to induce subsequent elimination of the reactivated cells by immune responses or virus-induced cytopathic effects (the "kill" phase). Studies using immunomodulatory LRAs such as blockers of immune checkpoint molecules, toll-like receptor agonists, cytokines and CD8 + T cell depleting antibodies showed promising potential as LRAs inducing directly or indirectly cellular pathways known to control HIV transcription. However, the precise molecular mechanisms by which these immunomodulatory LRAs reverse latency remain incompletely understood. Together with the heterogenous nature of HIV-1 latency, this lack of understanding complicates efforts to develop more efficient and safer cure strategies. Hence, deciphering those mechanisms is pivotal in designing approaches to eliminate latent HIV infection.